Maintenance Treatment with Opium Tincture: A Preliminary Qualitative Study of the Factors Related to Treatment entry. - Reza Daneshmand; Zahra Alam Mehrjerdi; Mercede Samiee (Tehran University of Medical Sciences, 2014)
The current preliminary study aimed to explore the reasons that a group of opiate-dependent patients reported for entry into opium tincture treatment (OTT).Through examinations of 52 qualitative focus group interviews with patients from six OTT centers and 10 health providers (in key informant interviews) in Tehran, this study highlights the factors that participants reported as the reasons associated with entry into OTT. Quantitative data including demographic data and details of drug use were analyzed by using SPSS.v.18.0. Qualitative data was analyzed by using Atlas-ti software.86.5% of patients were male and 13.5% were female. The median age of patients was 39 yr. The most frequently reasons associated with entry into OTT included methadone misconceptions including dissatisfaction with taking methadone as a chemical medication, methadone dependence, and long duration of MMT. The other reasons included the recommendation of other people in treatment and OT-related characteristics and expectations including the herbal compound of OT, treating opiate craving and withdrawal symptoms, and improving general health.The study findings preliminarily showed the reasons associated with entry into OTT in a sample of treatment seekers. Longitudinal studies with more representative samples and follow-up stages are required to evaluate the clinical effectiveness of OTT as a maintenance treatment in comparison with methadone and buprenorphine. Patient-centered program and policy implications are discussed.